Clinical Case Report: Secondary syphilis in a child with no history of sexual abuse - Fernandes, Regina Célia de Souza Campos; Medina-Acosta, Enrique (Brazilian Journal of Case Reports, 2024)
This pediatric case report details the diagnostic and therapeutic challenges of secondary syphilis in a six-year-old child presenting with oral lesions and perianal condyloma lata. The diagnosis was confirmed through the Venereal Disease Research Laboratory (VDRL) test, and successful treatment was achieved with benzathine penicillin. The case presented significant diagnostic complexities, necessitating the evaluation of three potential transmission routes: late congenital syphilis, sexual abuse, and non-sexual transmission. Late congenital syphilis was excluded based on the absence of typical symptoms such as bone and dental abnormalities and neurosensorial deafness. Sexual abuse was thoroughly investigated and ruled out following an extensive four-month evaluation by a multidisciplinary team comprising a psychologist, nurse, social worker, and pediatric infectious disease specialist. Ultimately, non-sexual transmission, likely from an untreated family member, emerged as the most plausible cause, supported by the observation of overcrowded living conditions and inadequate hygiene practices in the child’s environment. This case underscores the necessity of comprehensive diagnostic evaluations, including consideration of all possible transmission routes, in managing pediatric syphilis. Public health interventions focusing on improving living conditions and hygiene practices are essential to prevent similar cases.